Usulan Perbaikan Tata Letak Kerja Proses Produksi Lempengan Paku Bumi menggunakan simulasi Promodel (Studi Kasus: PT GCE) - Prastiyo, Muhammad Rizky; Sahroni, Nur; Rizky, Muhammad; Albani, Nabila Tiara (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Increasingly tight competition in the business world encourages organizations to improve the quality of their output. PT GCE, a manufacturing company in the Sheet Metal industry, with output based on employment. In the manufacturing process various obstacles often arise which result in delays in the processing time. To address these issues, they use computer simulations, primarily ProModel, to identify and overcome bottlenecks in resource utilization, production capacity, and inventory levels. This research focuses on PT GCE and queuing problems caused by several production processes, with the author analyzing the use of ProModel to improve production systems and increase performance. As a result of this research, the author made improvements to the production process system in order to increase performance, which can be done by increasing the number of employees or operators on machines where there is a buildup of goods, combining the Welding and Fit Up processes in order to optimize production time and areas as well as bringing work stations closer together with related processes and optimize operator performance so there is no waiting time. Keywords: Computer Simulation, Factory Layout, ProModel